Complications following laryngeal sacculectomy in brachycephalic dogs. (19th October 2017) - Hughes, J. R.; Kaye, B. M.; Beswick, A. R.; Ter Haar, G.
Abstract : Objectives: To evaluate the effect of sacculectomy on the immediate postoperative complication rate in dogs affected with brachycephalic obstructive airway syndrome. Materials and Methods: Retrospective review of clinical records of brachycephalic dogs with everted saccules that underwent surgery for brachycephalic obstructive airway syndrome between 2009 and 2014. Dogs were grouped as those having nares resection and staphylectomy only and those having nares resection, staphylectomy and laryngeal sacculectomy. Complications were scored as mild, moderate or severe. Results: In total, 37 dogs were included in the sacculectomy group and 44 in the comparator group. Dogs that had undergone sacculectomy were more likely to develop postoperative complications, with 18 of 37 developing complications, nine of which were moderate to severe. In the group without sacculectomy, nine of 44 dogs developed complications, of which one was severe. Different breed distribution between groups might also impact this outcome. Clinical Significance: The results suggest that sacculectomy might increase morbidity following brachycephalic airway surgery, but repeat studies are required to confirm this result. Further information is also required to determine whether the short‐term risks of sacculectomy are outweighed by superior long‐term functional outcome.